ALA Bulletin. (Chicago, Ill : American Library Association.)
For a full record of the library's holding apply to the circulation desk.Libraries and Civil Defense, Jane Fiquet Hanna
Midwinter meeting information will be found on pages 1171-73
Superseded by American libraries beginning 1970
Keywords: Library science -- Periodicals